G587 How relevant are low levels of vitamin D to radiological skeletal change and a potential risk of fracture: a retrospective study in a tuberculosis clinic. (27th April 2016) - Raychaudhuri, R; Demetriou, A; Bhatt, R; Jeyalingam, L; Conder, G; Pal, M; Williams, M; Michie, C; Williams, B
Abstract : Background: The significance of reduced vitamin D (25-OHD) to skeletal health, as assessed by radiological changes and fracture risk, is not known in detail. The uncertainty of this nutritional interaction becomes critical for instance in cases of potential non-accidental fracture. In order to provide an insight into this area we studied a paediatric group at high risk of low vitamin D levels. Aims: We aimed to estimate the incidence of radiological bony changes in patients attending a paediatric tuberculosis clinic, many of whom have chronically low vitamin D levels. Secondary outcomes were to assess whether serological markers of bone health can be used to identify those at greater risk of osteopenia and rickets. Methods: Children attending a paediatric TB clinic between 01/01/2008 and 31/12/2011 had blood samples, including serum vitamin D levels, and chest radiograph taken as part of routine investigation at diagnosis. All radiographs were reported independently and retrospectively by two consultant radiologists, who were blinded to the child's vitamin D status, on the presence of osteopenia or rickets. Results: 174 children were included in this study (46.6% male, median age 7 years range, 0.25–16y). At the point of diagnosis, 35 children were 25-OHD deficient (levels <25nmol/l), 57 were insufficient (levels 25–49nmol/l). During the study none of the cases suffered fracture and none had clinical evidence of rickets. Osteopenia was reported in one child by one radiologist. This child had a vitamin D level of 22 nmol/l and a raised PTH at 36.9. PTH levels were normal in 92 children, unavailable in 45 and raised in 30 children, of whom 29 had normal radiological skeletal appearances. A significant correlation between 25-OHD and PTH was identified (r=–0.371, 95% CI –0.5105 to –0.2123, p value <0.0001). Two children had hypocalcaemia with vitamin D deficiency but had normal PTH and alkaline phosphatase levels. There was no correlation between serum 25-OHD levels and alkaline phosphatase levels. Conclusion: The low incidence of radiographic bony abnormality and absence of fractures in a cohort of children with vitamin D deficiency, suggests many children with low serum vitamin D levels are unlikely to develop rickets and fractures.